Afiksasi Inflektif Verba Perfek dalam Naskah Drama Ahlul Kahfi Karya Taufiq al-Hakim - Khairina Nasution; Khairawati (CV. Creative Tugu Pena, 2026)
Arabic is characterized a highly systematic and productive morphological system particularly in the inflection of verbs to mark grammatical categories such as person, number, and gender. Although studies on Arabic morphology have been widely conducted research focusing specifically on inflectional affixation in perfect verbs within Arabic literary texts remains limited. This study aims to reveal the forms and functions of inflectional affixation in perfect verbs found in drama script Ahlul Kahfi by Taufil al-Hakim from a structural morphology perspective. This study employed a qualitative approach with a library research design. The data consisted of a perfect verbs undergoing inflectional affixation in 120 dialogues from the first part of the drama script. Data were collected through observation and note-taking techniques and analyzed using the distributional method with immediate constituent analysis technique. The findings revealed 71 perfect verbs with inflectional affixation based on variations of person, number, and gender. The inflectional formswere realized through suffixes such as /-tu/ (تُ), /-nā/ (نا), /-ta/ (تَ), /-tumā/ (تُمَا), /-t/ (تْ), /-tā/ (تَا), and /-ū/ (وا). The dominance of first person singular forms indicates that the dialogues are primarily constructed through the characters subjectivity. The findings demonstrate that inflectional affixation functions not only as a grammatical marker but also as a means of expressing interpersonalrelations and communication dynamics in drama. This study contributes to Arabic morphological studies, whilefuture researchmay examine other Arabic literary texts to obtain a broader understanding of Arabic verbal morphology.